Penyebab Menarche Dini Ditinjau Dari Status Gizi Dan Riwayat Keluarga Pada Siswi SDN 169 Pekanbaru - Andriani Andriani (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2022)
ABSTRACT Background: Background: Menarche is the first menstruation that occurs in every woman at different ages which generally occurs at the age of 12 years. Early menarche is the first menstruation that occurs in women under the age of 12 years which is influenced by several factors. In Indonesia, the youngest age of menarche is 9 years and the oldest is 18 years. Purpose: The purpose of this study was to determine the cause of early menarche in SDN 169 Pekanbaru students from nutritional status and family history, by taking primary data obtained directly from respondents. Method: Methods: This type of research uses quantitative with descriptive design. In this study, all students of SDN 169 Pekanbaru who had experienced menarche with the age of less than 12 years, were taken by means of a saturated sample with a total of 20 female respondents. Data processing is done manually and data analysis shows the results of the calculation of the frequency and percentage of results from the study. Results: The majority of female students who experienced early menarche in terms of nutritional status were 11 people (55%) with normal body mass index and viewed from family history as many as 10 people (50%) with family history of early menarche. Conclusion: Based on the results of this study it can be concluded that the most common cause of menarche early is due to the nutritional status of 11 people (55%). It is expected that this research for students of SDN 169 Pekanbaru can provide additional information about the causes of early menarche in terms of nutritional status and family history for students to know exactly what causes them to experience early menarche Keyword: Causes, Schollgirl, Early Menarche